Mitochondrial DNA copy number in cumulus granulosa cells as a predictor for embryo morphokinetics and chromosome status. (4th March 2023) - Rahmawati, Pitra; Wiweko, Budi; Boediono, Arief
Abstract: While morphokinetic evaluation of embryos has become the most commonly used technique in IVF to select embryos for transfer, studies have demonstrated that mitochondrial DNA (mtDNA) copy number is correlated with embryo viability and transfer outcomes. Correspondingly, this cohort study aims to evaluate the association between the mtDNA copy number in cumulus granulosa cells (CGCs) with embryo morphokinetic parameters and chromosomal status. Real-time PCR was employed to measure the mtDNA copy number of the 129 CGCs in samples obtained from 30 patients undergoing the IVF-IMSI program at Morula IVF Jakarta between July and October 2020. Bivariate and multiple analyses were utilized to determine its relationship with embryo morphokinetics, blastocyst yield, and chromosomal status. According to the analysis, there was a significant correlation between the mtDNA copy number and the blastocyst status after adjusting for the maternal age and sperm morphology (coefficient 0.832, p value = 0.032, RR value 2.299). Moreover, a significant link was observed between mtDNA copy number in CGC and early embryo developmental phase M1 (t2–t8), using the equation of M1 is 5.702–0.271 mtDNA copy number of CGCs + 0.017 maternal age + 0.013 sperm motility –0.115 sperm morphology ( p value = 0.032). However, no correlation was found between the mtDNA copy number in CGCs with the other morphokinetic parameters (M2: tC–tEB, M3: t2–tEB, DC, RC, MN with p  > 0.05), or the chromosomal status of the embryos (euploid: 139.44 ± 133.12, aneuploid: 142.40 ± 111.30, p  = 0.806). In conclusion, our study suggests that mtDNA copy number in CGCs can serve as a useful biomarker for blastocyst status and early embryo developmental phase but not for chromosomal status.